Dampak Aktivitas Pertambangan Batu Gamping Terhadap Kondisi Sosial Ekonomi Petani Cengkeh: Studi Kasus Kawasan Lingkar Tambang PT. MBN Kecamatan Bungku Timur Kabuapten Morowali - Alfina Alfina; Abdul Gafaruddin; La Ode Alwi (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
This study aims to (1) determine the impact of limestone mining activities on the socio-economic conditions of clove farmers in Lahuafu Village and Kolono Village, Morowali Regency, (2) determine the income of clove farmers in affected villages, namely Lahuafu Village and the income of clove farmers in unaffected villages, namely Kolono Village for PT MBN (Mineral Bumi Nusantara) limestone mining activities. This research was conducted in Lahuafu Village and Kolono Village, East Bungku District, Morowali Regency from August to October 2023. This type of research uses qualitative data analysis which is strengthened by quantitative data analysis with a total of 43 respondents. With data collection techniques carried out by observation, interview and documentation methods. To determine the economic impact, an independent sample t-test analysis was used to determine whether or not there was a difference in income between the income of clove farmers in Lahuafu Village and Kolono Village. The results showed that the existence of limestone mining activities in Lahuafu Village has positive and negative impacts on the socio-economic conditions of clove farmers in Lahuafu Village and Kolono Village. The social conditions of clove farmers have positive and negative impacts on changes in education levels, health, living conditions and employment opportunities. In addition, the presence of limestone mining has a positive and negative impact on increasing the income of clove farmers in the affected village of Lahuafu Village and the unaffected village of Kolono Village